Penambangan Ilegal Di Kecamatan Saronggi Kabupaten Sumenep dan Faktor-Faktor Yang Mempengaruhinya (RechtJiva, 2024)
This study aims to examine the effectiveness of the regulation found in Article 35 of Law No. 3 of 2020 in Sumenep Regency. The chosen research method is socio-legal, utilizing a sociological juridical approach. Data collection was conducted through interviews and literature studies. The findings of this study indicate that the implementation of the regulation in Article 35 of Law No. 3 of 2020 is ineffective. This ineffectiveness may be attributed to cultural factors, legal factors, infrastructure, law enforcement, and community factors. In this issue, the government's role has not been substantial in imposing legal sanctions on illegal mine owners. Additionally, the community tends to view mining as a source of employment, with those who are less tolerant and permissive toward illegal mining not considering the long-term consequences. The obstacles encountered include the community's difficulty in obtaining permits, even though the land used is privately owned.